Perencanaan Sistem Penyaluran Air Limbah di Kecamatan Sumbersari Kabupaten Jember - Dewi, Fauziah Rachma; Badriani, Ririn Endah; Kartini, Audiananti Meganandi (Universitas Trunojoyo Madura, 2023)
An increase in domestic wastewater if it isn’t treated properly, will potentially lead to a decrease in water quality. Existing conditions in Sumbersari Sub-district based on the preliminary survey, the domestic wastewater disposal is still mixed with the drainage network. This sewer then directly channeled into the water body without any prior treatment, this’s contrary to the PUPR Ministerial Regulation No.4 of 2017. The planning aims to network planning of Wastewater Distribution System in Sumbersari District. The planning service area is carried out in Sumbersari Sub-district, Antirogo Village isn’t included because it has the lowest population density and topography isn’t possible to be served. The planned wastewater is just graywater wastewater. The planning results concluded that the average wastewater discharge and peak wastewater discharge are around 178.19 L/s and 459.28 L/s. The planning is divided into 6 blocks and there’re 3 WWTPs to service the area. The planned pipe dimensions are 90-600 mm. There’re 3 pumps, 10 siphons, and 331 manholes for complementary building requirements. The total cost required for this planning is Rp53,477,911,716.